New frontiers in educational planning and curriculum reform in Trinidad and Tobago - London, Norrel A. (1989)
This article discusses the criticized shift system for junior secondary schools in Trinidad and Tobago. This system, which was established to meet the demands for additional school places, provides education for increased numbers of students by the same teachers, using the same classrooms and teaching materials, in a morning and an afternoon shift. Topics discussed include schools going to deshift, role of the education planner, curriculum reform, and students' well-being
Keywords: Junior secondary schools